ANALYSIS OF GROWTH AND INSTABILITY OF JOWAR AREA AND PRODUCTION IN ANDHRA PRADESH - D. SRINIVASA CHARY, T.M. DINESH, K. SUHASINI, B. DAYAKAR RAO, I. S.RAO and (The Journal of Research, PJTSAU, 2019)
Millets are group of small grained cereal food crops which are highly nutritious and are grown under marginal/low fertile soils with very low inputs such as fertilizers and pesticides. These crops largely contributeto food and nutritional security of the country. Most of millet crops are native of India and are popularly known as Nutri-cereals as they provide most of the nutrients required for normal functioning of human body. Further, the nutritional value of these crops offers much scope for development of value-added products in new health conscious consumer segments. Coarse cereals, namely sorghum, pearl millet and finger millet assume significance in the cropping pattern of dryland regions as they require little inputs and are more drought resistant compared to other competing crops (Breese, et al., 2002). Among which jowar is the most important food and fodder crop of dry land agriculture of Andhra  Pradesh. The crop is perennial in nature and possessing corn like leaves and bearing the grain in a compact cluster. Out of the total production of jowar in the nation, 52 % is from Maharashtra. Karnataka, Andhra Pradesh and Tamil Nadu. One more advantage of this crop is that it can be grown in both Kharif and Rabi seasons. Also, it can handle and growon a wide range of soil types starting from fertile to fewer nutrient soils but an effective output largely depends on soil moisture, resistance and porosity. This crop was favoured due to its productivity and short growing season under dry, high-temperature conditions. However, the last few decades saw this crop losing area on account of declining demand due to change in food habits and due attention has been given to cereals and commercial crops cultivation in Andhra Pradesh, that resulted in drop in real prices vis-a vis other competing crops leading to erosion in relative profitability of this crop.